RETRACTED: Appraising and reacting to voluntary green behavior at work: The effects of green motive attribution - Zhang, Xue; Li, Zhongqiu; Zhang, Huilai; Zhang, Qiwen (Frontiers in Psychology, 2022)
Starting from the perspective of social perception of voluntary employee green behavior (VEGB) and studies on the attribution of VEGB, we explore the phenomenon that employees can show different perceptions and behavioral responses to VEGB according to their attribution to VEGB. We surveyed to examine the hypotheses. The results of a two-wave study show that when employees believe VEGB is motivated by instrumental concerns, VEGB is more likely to evoke a low level of warmth and competence, which produces less green advocacy. However, if employees believe VEGB is motivated by moral reasons, VEGB will be more likely to prompt more warmth and competence perceptions and elicit greener advocacy from employees. Theoretical and practical contributions are discussed.